Loop diuretics decrease the renal elimination rate and increase the plasma levels of trimethylamine‐N‐oxide. (6th September 2018) - Latkovskis, G.; Makarova, E.; Mazule, M.; Bondare, L.; Hartmane, D.; Cirule, H.; Grinberga, S.; Erglis, A.; Liepinsh, E.; Dambrova, M.
Abstract : Aims: Trimethylamine‐N‐oxide (TMAO) is a novel cardiovascular risk marker. We explored the association of commonly used cardiovascular medications with TMAO levels in patients and validated the identified associations in mice. Methods: Detailed history of drug treatment was recorded in 300 patients with cardiovascular disease without diabetes in an observational, cross‐sectional study. Animal study was performed in CD1 mice. Results: Median plasma TMAO (interquartile range) level was 2.144 (1.570–3.104) μmol l –1 . Among nine cardiovascular drug groups, the use of loop diuretics (0.510 ± 0.296 in users vs . 0.336 ± 0.272 in nonusers, P =  0.008) and mineralocorticoid receptor antagonists (0.482 ± 0.293 in users vs . 0.334 ± 0.272 in nonusers, P =  0.007) was associated with increased log‐TMAO. Acute concomitant administration of furosemide or torasemide with TMAO in mice significantly influenced TMAO pharmacokinetic profile and almost doubled the plasma TMAO area under the curve. Furosemide decreased the TMAO excretion rate by 1.9‐fold during the first 30 min after administration and increased TMAO concentrations in kidney, heart and liver, suggesting the interaction of furosemide and TMAO with efflux transporters. The concentrations of TMAO in blood plasma after the administration of the organic anion transporter inhibitor probenecid were not different from those of the control group, suggesting an effect not mediated by organic anion transporters. Conclusions: Loop diuretics increased plasma TMAO concentration by decreasing its urinary excretion rate. Loop diuretic use should be considered a potential confounder in TMAO studies.